Stigma of Treatment Stages for First-Episode Psychosis: A Conceptual Framework for Early Intervention Services. Issue 2 (March 2021) - Yang, Lawrence H.; Blasco, Drew; Lieff, Sarah A.; Le, PhuongThao D.; Li, YiPing; Broeker, Marianne; Mascayano, Franco; Bello, Iruma; Nossel, Ilana; Dixon, Lisa
Abstract: Early intervention services (EIS; in the United States, Coordinated Specialty Care) can lead to substantial improvements in psychiatric symptoms and social functioning for individuals with first-episode psychosis who engage in treatment. Nevertheless, stigma associated with early intervention services can limit their full potential benefits by preventing or reducing participation. Drawing from Corrigan's "why try" model positing relationships between public and self-stigma, engagement in treatment services, and the EIS treatment model, this article proposes a framework that delineates how distinct forms of stigma are linked to given stages of treatment engagement in first-episode psychosis. We identify three phases of engagement: (1) community outreach, which has associations with public stigma; (2) the referral and evaluation process, which primarily has associations with self-stigma; and (3) EIS, which have associations with self-stigma and its psychosocial consequences. For each phase, we describe evidence-based strategies typically provided by EIS programs, using OnTrackNY as an exemplary model, to illustrate potential linkages in our conceptual framework. By specifying how distinct forms of stigma are associated with EIS treatment stages, this framework is intended to guide EIS programs in explicitly addressing stigma to optimize recovery of individuals with first-episode psychosis.